Lexical Tones in Mandarin Chinese Infant-Directed Speech: Age-Related Changes in the Second Year of Life - Han, Mengru; de Jong, Nivja H.; Kager, René (Frontiers in Psychology, 2018)
Tonal information is essential to early word learning in tone languages. Although numerous studies have investigated the intonational and segmental properties of infant-directed speech (IDS), only a few studies have explored the properties of lexical tones in IDS. These studies mostly focused on the first year of life; thus little is known about how lexical tones in IDS change as children’s vocabulary acquisition accelerates in the second year (Goldfield and Reznick, 1990; Bloom, 2001). The present study examines whether Mandarin Chinese mothers hyperarticulate lexical tones in IDS addressing 18- and 24-month-old children—at which age children are learning words at a rapid speed—vs. adult-directed speech (ADS). Thirty-nine Mandarin Chinese–speaking mothers were tested in a semi-spontaneous picture-book-reading task, in which they told the same story to their child (IDS condition) and to an adult (ADS condition). Results for the F0 measurements (minimum F0, maximum F0, and F0 range) of tone in the speech data revealed a continuum of differences among IDS addressing 18-month-olds, IDS addressing 24-month-olds, and ADS. Lexical tones in IDS addressing 18-month-old children had a higher minimum F0, higher maximum F0, and larger pitch range than lexical tones in ADS. Lexical tones in IDS addressing 24-month-old children showed more similarity to ADS tones with respect to pitch height: there were no differences in minimum F0 and maximum F0 between ADS and IDS. However, F0 range was still larger. These results suggest that lexical tones are generally hyperarticulated in Mandarin Chinese IDS addressing 18- and 24- month-old children despite the change in pitch level over time. Mandarin Chinese mothers hyperarticulate lexical tones in IDS when talking to toddlers and potentially facilitate tone acquisition and word learning.